FRI0347 Risk of Cardio- and Cerebro-Vascular Events in Patients with Rheumatoid Arthritis on Treatment with Tocilizumab or Etanercept. Retrospective Cohort Study on Health Administrative Databases of the Italian Society for Rheumatology (SIR). (9th June 2015) - Carrara, G.; Generali, E.; Selmi, C.; Scirè, C.A.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased cardiovascular (CV) morbidity and mortality.[1-2] Some drugs have been implicated in the increase of this risk, and in particular it has been recently suggested that the modifications of lipid profile observed during treatment with tocilizumab (TCZ) may increase the CV risk in patients with RA. Objectives: This analysis evaluates the risk of hospitalization for cardio-cerebrovascular events (CCV) in patients with RA treated with TCZ compared with ETA in clinical practice. Methods: Data including demographics, drug prescriptions, out-patient services and hospital admissions were extracted from the administrative health databases of Lombardy Region for the period between 1/1/2011 and 31/12/2013. Patients with RA were identified through a validated algorithm [3]. RA patients with a new course of treatment with TCZ or ETA were included. Hospitalizations/deaths for CCV events were evaluated through Hospital Discharge Forms based on relevant ICD-9CM codes (410*-1*, 413*, 431*, 433*-5*) and Disease-Related Groups (121-3, 140, 014-5). The association between exposure to TCZ and ETA on the risk of hospitalization for CCV event was assessed by survival models for competing risks and the results presented as hazard ratios (HR) and 95% CI, crude and adjusted for pre-specified confounders (sex, age, disease duration, use of methotrexate, corticosteroids, NSAIDs, number of previous biologics previous, presence of hypertension, dyslipidemia, diabetes). Sensitivity analyses on unmeasured confounding were performed. Results: A total of 666 patients treated with TCZ and 1086 with ETA were included in the analyses. In the TCZ group 13 CCV events (8 Cardio- and 5 Cerebro-vascular) in 12 patients /2124.5 person-year occurred, while in the ETA group 28 (19 and 9) in 27 patients/1187.1 person-year. At baseline, TCZ vs ETA group showed higher prevalence of women (81.8% vs 70.8%, p<0.001), older age (mean (SD) 57 (13) vs 55 (13) years, p=0.02), longer disease duration (median (IQR) 5.6 (2.9-6.8) vs 5.1 (2.2-6.4) years, p=0.006), previous biologics (median (IQR) 1 (0-1) vs 0 (0-1), p<0.001), concurrent NSAIDs (73% vs 63.5%, p<0.001), corticosteroids (72% vs 58.8%, p<0.001); no difference were found in terms of concurrent MTX (55% vs 57.4%), hypertension, diabetes and dyslipidemia. Using ETA as reference, TCZ was associate with a non-statistically significant reduction of the risk of CCV events (HR (95%CI) 0.49 (0.24-1)) (Table ). Having observed this HR, sensitivity analyses indicated that a theoretical increase of the CV risk associated with TCZ would be possible only in presence of a complete unbalance of an unmeasured confounder carrying a 5-fold increase of CCV. Conclusions: Treatment with TCZ is not associated with an increase in hospitalizations for CCV events compared with ETA in the medium term in clinical practice. Long-term pharmacoepidemiology registers and large simple trials will further define the CV safety profile of TCZ in RA. References: Carrara G, Scirè CA, Zambon A, et al. BMJ Open. 2015. PMID: 25631308. Humphreys JH, Warner A, Chipping J, et al. Arthritis Care Res (Hoboken). 2014. Sep;66(9):1296-301. Franklin J, Farragher TM, Lunt M, et al. Ann Rheum Dis. 2010 Sep;69(9):1660-4. Disclosure of Interest: None declared